DEVELOPMENT OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN THE ERA OF SOCIETY 5.0 - Fahri, Adnan Faishol; Azani, Mohammad Zakki (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2023)
The purpose of the research is to be able to provide knowledge for the problem of the Development of Islamic Religious Teachers. The development of Islamic Religious Education Teachers in the Era of Society 5.0